THE PRINCIPLE OF INEVITABILITY AND THE INSTITUTION OF EXEMPTION FROM LEGAL LIABILITY:: ASPECTS OF THE RELATIONSHIP - Y. Shevchenko, Anatolii; V. Kudin, Serhii; M. Loshchykhin, Oleksandr; H. Fatkhutdinov, Vasyl (Revista Gênero e Interdisciplinaridade, 2021)
The relevance of the research problem is due to the need for theoretical justification of the diversity of aspects of the relationship between the principles of inevitability and the institution of exemption from legal liability. The purpose of the article is to identify the essence of the relationship between the principles of inevitability and the institution of exemption from legal liability. The leading methodological approach of the research is the structural-functional approach, which allows to consider the principles of inevitability and the institution of exemption from legal liability as elements of the normative part of the legal system, which have their own functional purpose. The article reveals the essence of the principle of inevitability of legal liability; the content of the institute of exemption from legal liability is clarified; aspects of the relationship between the principle of inevitability of legal liability and the institution of exemption from legal liability have been established.